2009
DOI: 10.1002/lary.20166
|View full text |Cite
|
Sign up to set email alerts
|

Necrosis of the long process of the incus following stapes surgery: New anatomical observations

Abstract: These observations indicate that conclusions drawn from classical anatomical works appear to need reconsideration. The present authors consider that the reason for the necrosis of the long process of the incus is not a compromised blood supply, except in some exceptional anatomical situations. They discuss the possible reasons why malcrimping may lead to necrosis of the long process of the incus. To prevent such malcrimping, attention is paid to the new generation of prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…We preferred the 0.6-mm diameter piston, but a successful outcome has also been reported with the application of piston diameters in the range 0.4-0.8 mm [12,13]. Some authors attribute incus necrosis to the extensive application of lasers surrounding the long process of the incus, whereas we agree with those authors who consider this phenomenon to be due to a foreign body reaction [14][15][16]. We previously demonstrated that there was no suspicion of incus necrosis in the mid-term follow-up hearing results in 44 [3].…”
Section: Discussionmentioning
confidence: 56%
“…We preferred the 0.6-mm diameter piston, but a successful outcome has also been reported with the application of piston diameters in the range 0.4-0.8 mm [12,13]. Some authors attribute incus necrosis to the extensive application of lasers surrounding the long process of the incus, whereas we agree with those authors who consider this phenomenon to be due to a foreign body reaction [14][15][16]. We previously demonstrated that there was no suspicion of incus necrosis in the mid-term follow-up hearing results in 44 [3].…”
Section: Discussionmentioning
confidence: 56%
“…Instead, the mucosal network over the incus and the incudostapedial joint is usually supplied by other vessels from the posterior branch of the ATA. Nutritive foramina of the incus were also described by Gerlinger et al in a recent anatomical paper [10].…”
Section: Discussionmentioning
confidence: 68%
“…Several studies in the literature dealt with the issue of middle ear and ossicular chian vascularization [6][7][8][9][10], but the most influential one has been made by Nager and Nager in 1953 [11]. They traced blood vessels with a microscope, through serial histologic sections of 110 series of human temporal bone, providing, for each of the arteries of middle ear, a detailed description of the course, anastomoses, and branches, with particular regard to the blood supply of the auditory ossicles.…”
Section: Discussionmentioning
confidence: 99%
“…Necrosis of the LPI can occur after malcrimped stapes prosthesis or due to compromised blood supply of the incus. Gerlinger et al (17) observed the bony foramina of the feeding blood vessels of the LPI of 100 incudes and found up to 4 nutritive foramina on the LPI. The foramina were located anteromedially, mostly on the middle and cranial third of the LPI.…”
Section: Discussionmentioning
confidence: 98%